SOSIALISASI ANTI KEKERASAN SEKSUAL PADA ANAK USIA DINI DI MASJID AR-RAHMAN KELURAHAN LINGKAR BARAT KOTA BENGKULU - Syarifatun Nafsih; Rofiza Nabila; Ashab Bussoleh; Kurnia Susi Agustin; Melisa Puspita; Yolan Amanda Putri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Sexual violence against children and adolescents is a growing concern because it can cause long-term physical, psychological, emotional, and social impacts. Cases of sexual violence occur not only in public settings but also in environments considered safe and religious, such as houses of worship, Al-Quran Education Centers (TPQ), Islamic boarding schools, and other religious educational institutions. This situation demonstrates the importance of education and prevention efforts involving children, adolescents, parents, and the community. This community service activity aims to increase public understanding and awareness of the dangers of sexual violence and preventive measures. The activity was held on June 1, 2026, at the Ar-Rahman Mosque, Lingkar Barat Village, Bengkulu City, involving approximately 30 participants consisting of children, adolescents, and parents. The method used was participatory socialization and education through material delivery, discussion, and question and answer sessions. The results of the activity showed an increase in participants' understanding of the forms of sexual violence, its impacts, the importance of self-protection, and reporting mechanisms in the event of sexual violence. This activity is expected to be a preventive measure in creating a safe environment and supporting the protection of children from various forms of sexual violence.